DISINFECTION OF WATER USING ELECTROINTENSIVE PROCESSES - Moura de Melo, Cláudia (2013)
The realization of the photo-electrochemical process consists in percolating the solution to be treated through an electrolytic reactor, in which the anodes coated with metal oxides remains under the effect of ultraviolet radiation (UV). The solution used in this study was contaminated artificially from fecal samples positive for bacteria and intestinal parasites. The evaluation of the process for the disinfection of water was held in photo-electrical-chemical reactor, with a total volume of 10.0 Lper batch system contaminated with human fecal material. It was used as the -1supporting electrolyte solution of sodium perchlorate at 0.1 mol. Land applying a current density -1of 14 mAwith the aid of a source and a flow rate of 250 L.h. The UVradiation was provided by a mercury vapor lamp of 55 Wwithout bulb shield. The center electrode is inserted through a quartz bulb. Samples were analyzed for pH, conductivity, chemical oxygen demand (COD), and turbidity. Aspects of microbiological and parasitological parameters were treated for 0, 5, 10, 20, and 30 min.. After 30 min., 98.9% reduction in parasitic forms (cysts and eggs) was observed and 99.8% of the colony of Escherichia coliwas present. There was a reduction in COD values (65.7%) and turbidity (92.3%) of samples after treatment exposure, as a result of electrochemical oxidation of organic compounds dissolved in the medium.